Intense red photoluminescence and mechanoluminescence from Mn2+-activated SrZnSO with a layered structure. Issue 26 (13th June 2019) - Zhou, Yu; Yang, Yun-Ling; Fan, Yu-Ting; Yang, Woochul; Zhang, Wei-Bin; Hu, Jian-Feng; Zhang, Zhi-Jun; Zhao, Jing-Tai
Abstract : Intense red emitting Mn 2+ -activated SrZnSO samples were synthesized by solid-state reaction at high temperature, and their photoluminescence and mechanoluminescence properties were investigated. Abstract : A series of novel red emitting Mn 2+ -activated SrZnSO phosphors were successfully synthesized by solid-state reaction at high temperature. The photoluminescence (PL) and mechanoluminescence (ML) properties of these Mn 2+ -activated SrZnSO phosphors with different Mn 2+ concentrations were investigated. With increasing the concentration of Mn 2+ from x = 0 to 0.04, the unit cell volume increased from 153.82 to 154.19 Å 3 while the optical band gap decreased from 3.74 to 3.43 eV. The site occupation of Mn 2+ in the host lattice was demonstrated by Rietveld refinement, the electron paramagnetic resonance (EPR) spectrum, and the spectroscopic properties. A broad band emission peak at 603 nm of SrZn1− x Mn x SO (0.001 ≤ x ≤ 0.04) with an excitation wavelength of 318 nm was attributed to electronic transitions of Mn 2+ from the 4 T1 ( 4 G) level to the 6 A1 ( 6 S) level. The lifetime of SrZn1− x Mn x SO (0.001 ≤ x ≤ 0.04) decreased monotonously from 2.97 to 0.82 ms with increasing Mn 2+ concentration. In particular, intense emission of red light from SrZn1− x Mn x SO (0.001 ≤ x ≤ 0.04) under compressive load could be observed even with the naked eye, indicating that SrZn1− x Mn x SO could be used for stress sensors or stress imaging. There was a linear correlation between the ML intensity and external load in SrZn1− x Mn x SO, and the ML intensity could be recovered under UV light irradiation. Considering its advantages of non-destruction, reproducibility, and high ML intensity, SrZn1− x Mn x SO might be useful for non-destructive detection of stress.